PENDAMPINGAN MASYARAKAT DALAM PENYUSUNAN PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS PARTISPATIF DI SEKITAR WILAYAH PERTAMBANGAN DESA MATABURA KECAMATAN AMONGGEDO KABUPATEN KONAWE - Fitra Saleh; Jufri Karim; Erwin Anshari; Wahab Wahab; Marwan Zamili (Jurnal Pengabdian NUSANTARA, 2022)
Matabura Village is one of the villages located in Amonggedo District, Konawe Regency, which is located around the nickel mining area. One of the obligations of mining companies is to develop a Community Empowerment Program (CEP) based on the needs of the community around the mine. The purpose of this activity is to provide participatory-based community assistance whose final product is an inventory of community needs which will later be given to mining companies around Matabura Village to be included in the CEP document. The method used is through Focus Group Discussion (FGD) activities and interviews with a sample of 50 respondents. The results of this activity showed that there was a change in the area of the village boundary from 551 Ha to 399.40 Ha and the number of hamlets from 2 to 3 hamlets and the results of interviews and Focus Group Discussions (FGD) recommended programs to be proposed, namely: Scholarship Program, Repair of Places of Worship, Normalization rivers, Utilization of Human Resources, Sports Facilities, Changing Land Profits, Liming or dolomite on plantation land.